The sustainable and participatory city: A challenging concept! - Helga Kanning; Frank Scholles; Francois Mancebo (Cities and metropolises in France and Germany, 2022)
Sustainability and participation have become two priorities of urban policies. They are usually considered perfectly synergistic, but they are not. This chapter aims to disentangle the imbroglio of sustainability coupled with participatory processes in the theory and practice of urban planning and development. To do so, it reflects upon empirical observations in the field of public policies in France and Germany as well as on some cases on both sides of the Rhine. Finally, this chapter describes and analyses policies and governance instruments intended to involve citizens in sustainable decision-making in urban areas of France and Germany.
urn:nbn:de:0156-1119087; hdl:10419/266400; https://econpapers.repec.org/RePEc:zbw:arlfob:20
Keywords: 710; France; Germany; public participation; sustainable urban development; urban planning; Local Agenda 21